Study of the influence of the heat transfer coefficient on the evaporation process - Musaeva R.X; Musaeva N.X; Solieva O.K (International Consortium of Education and Culture Research Studies, 2020)
This paper makes analyses of the study while making comparisons of the influence of the heat transfer coefficient on the evaporation process. The way of the development and research analyses as the whole.